Implementation of online classes during national school closure due to COVID‐19 and mental health symptoms of adolescents: A cross‐sectional survey of 5000 students. Issue 2 (22nd June 2022) - Morishima, Ryo; Koike, Haruna; Kanehara, Akiko; Usui, Kaori; Okada, Naohiro; Ando, Shuntaro; Kasai, Kiyoto
Abstract: Aim: Online classes were implemented in numerous schools during the school closure due to COVID‐19. The present study examined the relationship between online classes during national school closure and mental health symptoms after the reopening of schools. Methods: We conducted a cross‐sectional survey from October 1 to November 7, 2020 using an anonymous self‐reported questionnaire to evaluate 21 junior and senior high schools in the Saitama prefecture of Japan. Out of the 5538 students who were recruited, 5000 agreed to participate. The relationship between the implementation of online classes and mental health symptoms (emotional symptoms, psychotic experience [PE], and smartphone addiction) was evaluated using mixed‐effect logistic regression models, while controlling for individual and class‐level covariates (e.g., gender, grades). Results: Implementation of online classes was reported by 78.2% of classroom teachers, and it was associated with lower rates of emotional symptoms (OR = 0.79, 95% CI = 0.63–0.99, p = 0.040) and smartphone addiction (OR = 0.79, 95% CI = 0.65–0.96, p = 0.020), but not related to PE (OR = 0.91, 95% CI = 0.61–1.36, p = 0.637). Conclusions: Implementing online classes during the national school closure might have had a potential protective effect for adolescents' mental health symptoms (especially emotional symptoms and smartphone addiction) after the reopening of schools during the ongoing COVID‐19 pandemic.